Current Issues of Familial Hypercholesterolemia: Features of Disorders of The Sympathetic Adrenal System and Cytokine Status - Vakhabov B.M (Genius Journals, 2023)
Presented the violations of the sympathetic adrenal system and cytokine status in patients with coronary heart disease in the family hypercholesterolemia. 154 men and women at the age of 18 to 65 years, with an average age 43,8 ±7,2 years and 15 practically healthy persons aged 20 to 50 years, with an average age 41,4 ±3,5 of the. Clinical, instrumental and special research methods were carried out. It was revealed that in the art of hypercholesterinemia, the pronounced changes of sympathetic adrenal system and cytokine status, which are more pronounced extent in patients with family hypercholesterolemia with clinical signs of CHD.
Keywords: Family hypercholesterolemia; coronary heart disease; cytokines